Análise de dados governamentais abertos de instituições federais de ensino superior (IFES) do estado de São Paulo - Romanin, Cristina Oliveira (Universidade Federal de São Carlos, 2025)
Accountability and transparency have been increasingly addressed in all areas of scientific knowledge, including Information Science. Open data has the potential to be used to support these concepts. The objective was to evaluate open data sets from Federal Universities in the state of São Paulo regarding their adherence to the FAIR principles from Force11 and the W3C Best Practices for Data on the Web. The method consisted of using a protocol in the form of a checklist, composed of questions based on these principles and best practices, which was applied to the data sets located on the Federal Government Open Data Portal. The results indicate that, although the institutions make their data available under open licenses, the potential for their location, access and reuse is compromised by the low use of permanent identifiers and good quality metadata. Conclusion: The use of data can boost and assist transparency and accountability in the Brazilian context, since, for action, it is necessary to have arguments evidenced by data, to support advocacy and public policies.
Analysis of open government data from federal higher education institutions (IFES) in the state of São Paulo
Keywords: Dados Governamentais Abertos; Universidades Federais; Accountability; Transparência; Nível de abertura de dados; Dados públicos; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::PROCESSOS DE DISSEMINACAO DA INFORMACAO